Measuring Brand Equity among Albanian Consumers - Rozana Haxhialushi; Vjollca Hysi Panajoti (European Scientific Journal, ESJ, 2018)
Brands offer advantages for consumers and companies and companies are spending a lot in creating and managing their brands. Brand equity and its dimensions have received a great attention from academics. The purpose of this paper is to test the proposed model to better understand brand equity among Albanian consumers. It investigates the hierarchy of brand equity dimensions and the effect these dimensions have on brand equity. Hypothesis were tested using structural equation modeling. The reliability of the model was assessed using confirmatory factor analysis. Results show that brand awareness has a positive effect on brand associations, brand associations positively affect perceived quality which is positively related to brand loyalty. All dimensions have a positive effect on brand equity. Items for measuring overall brand equity were used. This study contributes to the large body of literature on brand equity. It has limitations because we use two product categories and a limited set of brands.